Managing Unpredictability: The Intimate Public of Finnish Trans Memes on Instagram - Jaaksi, Vilja (Foreningen Lambda Nordica, 2025)
While research has delved into the political and protest potential of memes, the analyses have largely left out political memes of marginalized communities. This article provides an analysis of Finnish trans memes on Instagram, focusing simultaneously on their political arguments and on the intimate public formed around them. Based on 18 media diaries and interviews with Finnish gender minorities, this article explores how Finnish trans memes on Instagram articulate how unjust social infrastructures create vulnerability and unpredictability in trans lives, while at the same time creating feelings of connection between and across identities, and alleviating feelings of vulnerability through laughter and care. The article challenges the traditional notion of politics as being outside of intimate publics, arguing that Finnish trans memes’ articulation of the vulnerability and unpredictability resulting from unjust infrastructure is, in fact, the connecting glue of the intimate public.